INNOVATIVE METHODS OF PERSONNEL MANAGEMENT: AGILE SYSTEMS -TRANSFORMATION OF ORGANIZATION SBERBANK SCALE - L. Borisoglebskaya; E. Shikova (Вестник университета)
The article deals with the relevance of topics of modernization of personnel management system, and shows the positive effects of the priority directions of the personnel management system. The analysis of innovative management practices in the banking sector and offered Agile project, allowing the Bank to start a large-scale conversion to flexible IT-enterprises that can adapt to rapidly changing environmental conditions.